From mistakes to mastery: students learn the art of opinion writing - Nurul Nadia, Muhammad; Siti Ainun Jariyah, Hassan (UMPSA, 2025)
PEKAN, 8 May 2025 – The ULE1310 Fundamentals of English Language and ULE1352 Essential English courses recently hosted a successful Global Classroom session via Google Meet. Specifically designed for Semester 2, Session 2024/2025 students, the interactive two-hour session welcomed 43 participants and ran from 8:30 p.m. to 10:30 p.m.